Fluoro-electrochemical microscopy reveals group specific differential susceptibility of phytoplankton towards oxidative damage. Issue 34 (17th July 2019) - Yang, Minjun; Batchelor-McAuley, Christopher; Chen, Lifu; Guo, Yanjun; Zhang, Qiong; Rickaby, Rosalind E. M.; Bouman, Heather A.; Compton, Richard G.
Abstract : In the vicinity of an electrode creating a highly oxidising environment the fluorescence – arising from the presence of chlorophyll-a – of single cellular phytoplankton becomes inhibited. Abstract : In the vicinity of an electrode creating a highly oxidising environment the fluorescence – arising from the presence of chlorophyll-a – of single cellular phytoplankton becomes inhibited. Even for phytoplankton that are very comparable in size ( ca. 2–20 μm) the rate of this (electro)chemically induced fluorescence inhibition differs significantly between phytoplankton species; the fluorescence signal of the freshwater algae Stichococcus bacillaris turns off ∼70 times faster than that of the marine coccolithophore Emiliana huxleyi . The varying behaviour reflects the differing susceptibility of these globally important phytoplankton species towards extreme levels of radical induced oxidative stress, indicating the physical and chemical properties of the plankton cell wall and membrane are very different between species, and are important in determining their susceptibility. These results have potential implications for the analytical detection and characterisation of phytoplankton cells in the natural environment.